Growth and Fruit Yield of Okro as Influenced by Genotypes and Mulch in the Guinea Savannah Conditions of Ghana - Richard Yaw Agyare; Mashark Seidu Abdulai; Samuel Saaka Buah; Emmanuel Ayipio; Samuel Kwame Bonsu; Regine Tchientche Kamga (International Journal of Agronomy)
The experiment was carried out to assess the suitability of different mulch materials in enhancing the growth and fruit yield of okro. Ten okro genotypes were evaluated in a split plot design with 3 replications. Three treatments of mulch (black plastic, grass, and no mulch) represented the main plots with the genotypes as the subplots. The result indicated significant (P<0.05) genotypic variability among the genotypes for all parameters except plant girth. However, genotype and mulch interaction was not significant. The genotype Sasilon had the tallest plants (82.6 cm) and the highest fruit yield under all mulch conditions while Koni had the widest fruits (34.1 mm) with TZ SMN 10-3 having the longest fruits (16.11 cm). Number of fruits per plant ranged from 30 to 11 with an average of 21. Mulching significantly (P<0.05) influenced all parameters except fruit width and mean fruit weight. Plastic mulched plots had the greatest heights while no mulching had the least. The highest average yield was obtained under plastic mulch (3.49 t/ha) which was 4.2% higher than grass (3.34 t/ha) and 11% higher than no mulch (3.11 t/ha). The study has shown that mulching with black plastic or grass ensures vigorous growth and improves the fruit yield of okro.